2019
DOI: 10.1097/qad.0000000000002229
|View full text |Cite
|
Sign up to set email alerts
|

Hearing complaints in HIV infection originate in the brain not the ear

Abstract: Objective: Evidence suggests damage to brain auditory pathways, rather than inner ear damage, underlies the hearing difficulties HIV+ individuals report. But, anti-retroviral therapy (ART) may affect the hearing system and also lead to hearing complaints.Design: Longitudinal study of HIV+ and HIV-individuals in Dar es Salaam Tanzania. A subset of this cohort started ART while in the study allowing the effects of ART to be studied directly. Methods:The ability to hear quiet sounds (pure-tone audiometry), cochle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 11 publications
(19 reference statements)
2
31
0
Order By: Relevance
“…A variety of studies have hypothesized that HIV, while present in the CNS, has its direct effect on the vestibular and cochlear system as well as more central auditory processing pathways (13, 27, 28). As demonstrated by Matas et al and Maro et al MLR latencies and gap detection thresholds were prolonged as a measurement for central auditory processing (2, 13).…”
Section: Discussionmentioning
confidence: 99%
“…A variety of studies have hypothesized that HIV, while present in the CNS, has its direct effect on the vestibular and cochlear system as well as more central auditory processing pathways (13, 27, 28). As demonstrated by Matas et al and Maro et al MLR latencies and gap detection thresholds were prolonged as a measurement for central auditory processing (2, 13).…”
Section: Discussionmentioning
confidence: 99%
“…We also implemented an adaptive GAP test to evaluate temporal auditory processing. The adaptive gap detection algorithm applies a single staircase and has been used extensively in our previous studies [ 4 , 33 , 35 ]. In the algorithm, the gap length is shortened when the subject correctly identifies two gaps in a row.…”
Section: Methodsmentioning
confidence: 99%
“…This involves neural pathways throughout the brainstem and into the cortex that integrate with linguistic and cognitive systems, which depend on adequate processing speed, working memory, and attention [ 5 - 7 ]. In addition, previous studies have shown that HIV-positive individuals develop signs of central auditory processing that cannot be attributed to peripheral hearing loss [ 4 , 8 , 9 ]. Even with normal peripheral hearing sensitivity (eg, normal pure-tone auditory threshold test results), HIV-positive individuals show degraded results on tests of speech perception in noise [ 10 ] and auditory gap detection [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations